Distributed Transactions in Cloud Computing: A Review Reliability and Consistency - Ferzo, Barwar; Zeebaree, Subhi R. M. (AI Society & STMIK Indonesia, 2024)
The challenges of managing distributed transactions in cloud computing are discussed in this paper. The paper places an emphasis on the critical balance that must be maintained between reliability and consistency in the face of complexities such as hardware failures, network outages, and varying latencies. It sheds light on the delicate balance that must be maintained in order to guarantee that transactions in cloud environments are both reliable and consistent. Cloud environments are prone to hardware glitches and network disruptions. In addition, the paper delves into novel approaches with the objective of cultivating a computing ecosystem that is both resilient and dependable in the face of the ever-changing requirements of cloud computing, also a comparison table is presented for all the literature reviewed.